In Quest of Tablet Apps for Elders With Alzheimer's Disease: A Descriptive Review. Issue 7 (July 2021) - Tak, Sunghee H.
Abstract : Caregivers search for mobile device apps that offer meaningful and enjoyable activities to simultaneously enhance the preserved cognitive and functional abilities of those in their care. The purpose of this review article was to describe the current state of tablet apps with which elders with Alzheimer's disease and related forms of dementia may engage as users. Using the keywords "app, " "Alzheimer's, " and "dementia, " a sample of 83 apps was selected from the iTunes Store, Google, and discussion boards of Apple Support Communities. A descriptive content analysis was conducted using a coding scheme on the characteristics of tablet app activity and the requirements for functional abilities of the users. This review found that the activities of the selected apps included games, simple watching and viewing, music and sounds, memory training, learning and information, and social interaction starters. A high-level cognitive and physical ability such as eye-hand coordination is often required to play the majority of the game apps. A few apps are designed specifically for the population. Individuals' variability in cognitive and functional abilities necessitates a person-centered approach in designing and selecting games and activities for apps in order to increase engagement and promote positive experiences in older adults. Abstract : Supplemental digital content is available in the text.